Prevalence of symptom-based hand eczema among members of Filipino Chinese dental foundation - Haluag, Derrick Dee (Department of Community Dentistry, University of the Philippines Manila, 2019)
INTRODUCTION: Dentists have increased risk of developing hand eczema. Risk factors include repeated hand washing, frequent use of alcohol-based disinfectants and use of gloves for several hours. This study determined the 1-year prevalence of self-reported hand eczema among members of Filipino-Chinses Dental Foundation (FCDFI).